'Bin it and forget it!': The challenges of food waste management in restaurants of a mid-sized Hungarian city. (January 2021) - Filimonau, Viachaslau; Sulyok, Judit
Abstract: Although research on food waste and its management in foodservices is gradually evolving in developed countries, it remains limited in transitional economies. This holds true for many EU-28 member states located in East-Central Europe, where no studies have assessed to date the magnitude of food waste occurring in foodservices, identified its key drivers and established the scope for minimisation. By interviewing 18 managers of foodservice businesses in a historical, mid-sized, city of Veszprem, this paper explores the phenomenon of food waste in the foodservice sector of Hungary, an EU-28 economy in transition. It provides a first benchmark of food waste generation in Hungarian foodservices. It also identifies institutional, contextual, locational, organisational and cultural factors that impede food waste prevention and mitigation. Drawing on international experience and best practices in food waste management, recommendations are made on how these factors should be addressed. Highlights: Provides a first benchmark of food waste generation in Hungarian foodservices Identifies barriers to more effective management of food waste Categorises these barriers into institutional, contextual, locational, organisational and cultural Drawing on international experience, suggests how these barriers can be addressed.